BRIDGING THE GAP BETWEEN POLICY AND PRACTICE: AN EVALUATIVE STUDY OF MERDEKA CURRICULUM PLANNING IN INDONESIAN PRIMARY SCHOOLS - Erdiyanti, Erdiyanti; Hasri, Kharis Sulaiman; Rahmayanti, Wisna (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
This study aims to evaluate the implementation of the Merdeka Curriculum in primary schools. A qualitative approach with an explanatory case study design was used in three educational institutions in Southeast Sulawesi: SDN 2 Kendari, MIN 1 Kendari, and SDN 5 Landono. Data were collected through semi-structured interviews, observations, and analysis of teaching module documents. The results show that teachers have a basic cognitive understanding of key elements such as Learning Objectives (TP) and Learning Objective Flow (ATP), but the depth of meaning varies from administrative compliance to philosophical internalization. A phenomenon of ‘digital shortcuts’ was found, where teachers are highly dependent on modules from the internet due to a deficit in formal structural training. Document evaluation revealed inconsistent administrative quality, with some schools neglecting essential media and identity components. In conclusion, although teachers demonstrate ‘transitional literacy’ by mapping new concepts onto old structures, the sustainability of the Merdeka Curriculum requires intensive data-based instructional design training to reduce digital dependence and enhance pedagogical autonomy